Implementation Of Lean Process Management Through Enhanced Problem Solving Capabilities. - A. Perumal, Puvanasvaran (2009)
All Original Equipment Manufacturers (OEM) organizations in Aerospace, Automotive and Electronics industries had to upgrade their functions. These organizations including suppliers and solutions providers are duty bound to improve their functions through strategic initiatives. One such initiative is Lean Process Management. Lean Process Management has proven to aid organizations in developing manufacturing and administrative management solutions and make the organization a leaner at the same time a 'fitter' one, achieving World Class standards in terms of production, quality, marketing, etc, etc. The issue or problem is, although a number of authors, experts, researchers have discussed the lean process management as part organization centric issues, they failed to provide an effective lean process management system. Besides the need to formulate an effective lean process as suggested by some authors, another important reason suggested is the employee's development aspect regarding how to unlock the infinite potential of their workforce. This employee's development is basically the problem solving capabilities of the employees while implementing the Lean through clear cutting protocols or processes of Lean Process Management.